Literary Criticism in the Album Selamat Ulang Tahun—Nadin Amizah: An Expressive Approach - Devina, Nhaya; Fitriyah, Sarah Nur; Agus, Cecep (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
The research examines Nadin Amizah's album 'Selamat Ulang Tahun' through an expressive approach to literary criticism, focusing on how the artist's personal experiences and emotions are reflected in her songwriting. Born in 2000 in Bandung, Nadin's background as a child of divorced parents who primarily lived with her grandmother significantly influences her musical narratives. The album, consisting of nine songs including 'Bertaut,' 'Kanyaah,' 'Paman Tua,' 'Kereta Ini Melaju Terlalu Cepat,' 'Beranjak Dewasa,' 'Taruh,' 'Cermin,' 'Mendarah,' and 'Sorak Sorai,' explores themes of maternal love, family dynamics, personal growth, and emotional healing. Through detailed analysis of each song's lyrics, the study reveals how Nadin transforms her intimate experiences into universally resonant stories. The research particularly highlights her masterful use of metaphor and imagery to convey complex emotions, as exemplified in songs like 'Bertaut,' which uses the metaphor of intertwined heartbeats to describe the mother-daughter bond, and 'Cermin,' which employs mirror imagery to explore self-reflection and healing. The study concludes that Nadin's ability to weave her personal narrative into accessible, emotionally powerful lyrics contributes significantly to the album's widespread appeal among Indonesian audiences. This analysis demonstrates how the expressive approach to literary criticism can reveal the deep connections between an artist's lived experiences and their creative output, particularly in contemporary popular music.